Relationship between skeletal muscle mass and cardiac function during exercise in community‐dwelling older adults. (10th April 2017) - Sugie, Masamitsu; Harada, Kazumasa; Takahashi, Tetsuya; Nara, Marina; Ishikawa, Joji; Koyama, Teruyuki; Kim, Hunkyung; Tanaka, Jun; Fujimoto, Hajime; Obuchi, Shuichi; von Haehling, Stephan; Kyo, Syunei; et al.
Abstract: Aims: This study aimed to investigate the relationship between skeletal muscle mass and cardiac functional parameters in older adults during cardiopulmonary exercise testing (CPET). Methods and results: Sixty‐three Japanese community‐dwelling older adults were enrolled (20 men and 43 women; mean age 80 years, range 65–97 years). Cardiac functional parameters during exercise were assessed using CPET. Skeletal muscle mass index (SMI) was calculated by dividing the appendicular lean mass (measured using dual‐energy X‐ray absorptiometry) by height in metres squared. Subjects were divided into two groups: men with SMI ≥ 7.0 kg/m 2 and women with SMI ≥ 5.4 kg/m 2 (non‐sarcopenic group); or men with SMI < 7.0 kg/m 2 and women with SMI < 5.4 kg/m 2 (sarcopenic group). There were significant positive correlations between SMI and peak oxygen uptake (VO2 ) ( r = 0.631, P < 0.001), and between SMI and peak VO2 /heart rate (HR) ( r = 0.683, P < 0.001). However, only peak VO2 /HR significantly differed between groups in both sexes. Multiple linear regression analyses with peak VO2 /HR as a dependent variable showed that SMI was the only independent determinant after adjusting for potential confounders. After 4 month follow‐up of 47 participants, there was still a significant positive correlation between SMI and peak VO2 /HR ( r = 0.567, P < 0.001), and between percent change of SMI and percent change of peak VO2 /HR ( r = 0.305, P < 0.05). Conclusions: Peak VO2 /HR, an index of stroke volume at peak exercise, was associated with SMI. This indicates that skeletal muscle mass might affect cardiac function during exercise.